1978
DOI: 10.1038/icb.1978.59
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of Rat Liver Cell Multiplication‐stimulating Activity (Msa) to Human Placenta and Serum Proteins

Abstract: Summary Multiplication‐stimulating activity (MSA) from the medium of BRL‐3A rat liver cells in culture binds to cell membrane and cytosol receptors from human placenta and to serum proteins. The binding of MSA to placental cell membranes is dependent on time, temperature, pH and divalent ion concentration. MSA bound to placental cytosol receptor and serum is not displaced by insulin, whereas that bound to placental cell membranes is displaced by insulin and insulin‐like peptides. The affinity of the three rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The inter-and intra-assay variation were 13•1 % and 11•1 % respectively. The binding of 125I_MSA to unextracted foetal serum was performed as previously described (Brinsmead and Liggins 1978b). The ligand was first purified by binding to and eluting from foetal liver receptor.…”
Section: Glucose and Hormone Assaysmentioning
confidence: 99%
“…The inter-and intra-assay variation were 13•1 % and 11•1 % respectively. The binding of 125I_MSA to unextracted foetal serum was performed as previously described (Brinsmead and Liggins 1978b). The ligand was first purified by binding to and eluting from foetal liver receptor.…”
Section: Glucose and Hormone Assaysmentioning
confidence: 99%
“…Scatchard analysis of the 125I-labelled insulin binding and 125I-labelled IGF binding showed a curvilinear slope for 125I-labelled insulin binding indicating heterogeneity of the binding sites, and also a high-affinity, low-capacity and second low-affinity, high-capacity binding system for 125I-labelled IGF. Several classes of receptor with differing affinities have been described for IGF I (Daughaday, Mariz & Trivedi, 1981), multiplication stimulating activity (MSA) (Brinsmead & Liggins, 1978) and somatomedin C (D'Ercole, Underwood & Van Wyk, 1977). Therefore changes between the sub-classes of the IGF receptor with growth status may also explain the altered competitive binding by insulin.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative explanation arises from the work of Chochinov et al (1977) who reported that the major receptor assayable somatomedin in human amniotic fluid is a protein that binds labelled somatomedin Iigand and has no intrinsic growth-promoting properties. It is possible that such a binding protein may contribute to the activity measured by the receptor assay used in this study (Brinsmead and Liggins, 1978b). Heinrich et al (1978) recently reported substantial concentrations of a somatomedin-binding protein in human cord blood.…”
Section: Dlscusslonmentioning
confidence: 93%
“…SmLRA and SFA concentrations differed significantly in the 24 sera for which both assays were performed. The receptor assay detects several insulin-like peptides in serum (Brinsmead and Liggins, 1978b) whose concentrations may vary independently (Van Wyk et al, 1977). The sulphation factor bioassay in turn is influenced by a number of inhibitors which are not active in receptor assays, but which may be important in the physiological regulation of serum somatomedin activity (Salmon, 1975).…”
Section: Dlscusslonmentioning
confidence: 99%